9-[2-(Phosphonomethoxy)ethyl]adenine diphosphate (PMEApp) as a substrate toward replicative DNA polymerases alpha, delta, epsilon, and epsilon* - Birkus, G; Votruba, I; Holý, A; Otová, B (Biochemical pharmacology, 1999)
The diphosphoryl derivative of the acyclic nucleotide phosphonate analog 9-[2-(phosphonomethoxy)ethyl]adenine (PMEA), found previously to weakly inhibit DNA pol delta/proliferating cell nuclear antigen, was studied as a substrate for pol alpha, delta, epsilon, and epsilon*. A comparison of the Vmax and Km for this derivative (PMEApp) and dATP demonstrated that the relative efficiency of the incorporation of this analog into the DNA chain is decreasing in the following order: pol delta approximately equal to pol epsilon approximately equal to pol epsilon* > pol alpha. Under the reaction conditions, this incorporation amounted to 4.4 to 0.7% of dAMP molecules. Similar Km values for PMEApp and dATP in pol epsilon and pol epsilon* catalyzed reactions revealed that proteolysis of the enzyme probably does not affect the dNTP binding site. The DNA polymerases tested were inhibited by the reaction product (PMEA terminated DNA chain) with similar Ki/Km ratios (pol alpha 0.2; pol delta, 0.1; pol epsilon 0.05; and pol epsilon*, 0.06). The associated 3'-5'-exonuclease activity of pol delta, epsilon, and epsilon* was able to excise PMEA from the 3'-OH end of DNA with a rate one order of magnitude lower than that of the dAMP residue.
Keywords: substrátová specifita; potkani Sprague-Dawley; Organophosphonates; Rats; DNA-dependentní DNA-polymerasy; organofosfonáty; DNA-polymerasa I; Adenine; Animals; DNA Polymerase II; replikace DNA; DNA Replication; adenin; DNA Polymerase III; DNA-polymerasa II; zvířata; Substrate Specificity; DNA-polymerasa III; krysa rodu Rattus; DNA Polymerase I; DNA-Directed DNA Polymerase; Rats, Sprague-Dawley